IIR multiple notch filters design with optimum pole position - Yimman, Surapun; Praesomboon, Sukanya; Soonthuk, Parinya; Dejhan, Kobchai (My University, 2006)
The following article introduces the new design and implementation of IIR multiple notch filters by the application of suitable pole placement technique. The initial step is to design the two IIR single notch filters with difference notch frequency to find suitable pole that can control the pass-band gain at 3 frequencies such as DC, π and frequency between the notch frequency. After that, connect the IIR single notch filters with difference notch frequency in cascade to create IIR multiple notch filters which can control the pass-band gains at DC and π frequency especially the frequency between the notch frequencies. © 2006 IEEE.